Some Ethnomedicinal Plants of Bhardew village, Lalitpur District, Nepal - Gautam, Ratna Silwal; Shrestha, Sudha Joshi; Shrestha, Ila (Patan Prospective Journal, 2022)
This paper describes fifteen important ethnomedicinal plant species of Bhardew village of Lalitpur district. The several field visits were carried out during 2020 and 2021 to gather information from local people and key informants regarding the ethnomedicinal plants and their uses to cure various human diseases. On the basis of 25 common informants and five key informants total 15 ethnomedicinal plants were documented as very common and highly used medicinal plants. Some of the important medicinal plants were Artimesiadubia, Valerianajatamansi, Acoruscalamusand Urticadioica in the study area. Despite the fact that the study area is very close to the capital city, medicinal plants have played a significant role in the health care of the local people.